Learning from the news towards a comprehensive theory of motivational effects - David, Clarissa C. (2009)
While many research studies on political knowledge investigate how motivation can influence learning, the theoretical process of influence is yet to be mapped out. There are identifiable gaps in the existing literature, such as the conceptualization of motives, relationships between different motives, and their impacts on news seeking and learning outcomes. The author describes a process of learning comprised of distinct steps from exposure to knowledge, with each step viewed as a behavioral decision determined by the individual-level factors opportunity, ability, and motivation. Findings in the literature on knowledge gaps, uses and gratifications, and the information processing approach to learning are all brought to bear in developing an organized theory of motivational effects. A model that traces the influence of motivations on each step of the learning process is proposed. Such a model allows for a systematic examination of the many direct and indirect effects that motivations have on learning of political information from the news. Implications for Philippine communication research in the area of political learning from the news are discussed.
Includes bibliographical references (pages 26-32).
Keywords: Motivation (Psychology).